Direct introduction of R-SO2F moieties into proteins and protein-polymer conjugation using SuFEx chemistry. (2nd September 2016) - Li, Shaohua; Cohen-Karni, Devora; Beringer, Laura T.; Wu, Changgong; Kallick, Ethan; Edington, Howard; Passineau, Michael J.; Averick, Saadyah
Abstract: The modification of proteins with reactive handles has facilitated the use of these biomolecules in diverse fields including drug delivery, diagnostics, environmental remediation, and cell culture matrices. Recently, a new "click" type reaction, sulfur(VI) fluoride exchange (SuFEx), was reported between sulfuryl fluoride and various organic moieties (e.g. hydroxyl, amine) to yield a sulfamoyl fluoride (NSO2 F) or fluorosulfate (OSO2 F) moiety under biphasic conditions. The model protein bovine serum albumin (BSA) was reacted with SO2 F2 gas under biphasic conditions to yield SO2 F functionalized protein. The resultant BSA-SO2 F was characterized using gel electrophoresis, mass spectroscopy and Fourier transmission infrared spectroscopy to confirm the addition of SO2 F functional group. SuFEx modification of BSA caused a marked change in the pH dependent size and zeta potential of the protein as well as increased the protein's denaturation temperature. Crucially, BSA-SO2 F was demonstrated to be biocompatible after 72 h incubation with A549 lung endothelial cells. Due to the unique and elective reactivity of the SO2 F group with amines, BSA-SO2 F could be self-condensed to form a biocompatible hydrogel that was used in co-culture with HEK 293 cells. In addition, polyethylene glycol (PEG) with reactive OSO2 F groups at chain end was conjugated with BSA under various pH conditions through SuFEx chemistry. This communication, to our knowledge, is the first report of the application of the SuFEx in the field of bioconjugates. Graphical abstract: Highlights: Sulfuryl fluoride gas was reacted with bovine serum albumin to yield BSA-SO2 F. Bioconjugates could be formed through a SuFEx reaction between BSA-SO2 F and PEG-OTBDMS. SuFEx chemistry was used to self-condense BSA-SO2 F into biocompatible hydrogels.